2018
DOI: 10.5751/es-10504-230404
|View full text |Cite
|
Sign up to set email alerts
|

A framework for incorporating sense of place into the management of marine systems

Abstract: 2018. A framework for incorporating sense of place into the management of marine systems. Ecology and Society 23(4):4. https://doi.ABSTRACT. Successfully managing current threats to marine resources and ecosystems is largely dependent on our ability to understand and manage human behavior. In recent times we have seen increased growth in research to understand the human dimension of marine resource use, and the associated implications for management. However, despite progress to date, marine research and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…However, because sense of place is often intrinsically linked to cultural identity via history, social connections and personal understandings (Ryfield et al 2019;Song et al 2019), it can be a difficult feeling to articulate and quantify. Metrics of sense of place associated with marine environments are slowly being developed to better incorporate cultural values into marine management (van Putten et al 2018).…”
Section: Cultural Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because sense of place is often intrinsically linked to cultural identity via history, social connections and personal understandings (Ryfield et al 2019;Song et al 2019), it can be a difficult feeling to articulate and quantify. Metrics of sense of place associated with marine environments are slowly being developed to better incorporate cultural values into marine management (van Putten et al 2018).…”
Section: Cultural Connectionsmentioning
confidence: 99%
“…The benefits and experiences people derive from marine environments over periods of time build a fundamental sense of place, or deep-seated emotional bond with specific places and/or activities, thereby influencing environmental behaviours that can be regarded as cultural values (van Putten et al 2018 ). Developments in the emerging field of neuro-conservation have demonstrated that being near the ocean can foster strong emotional interest in marine environments, and also improve personal well-being (Nichols 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a rapidly advancing space, with many more models likely to have some capacity in this area in the near future, benefiting from increased attention being placed on understanding fisher behavior and the feedback between human users and ecosystem dynamics (e.g. Van Putten et al, 2018;Bourdaud et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging this "power of place" is posited as a valuable means to improve conservation decision making and increase participation in citizen science (Newman et al 2017). We identify this sense of place component as one that requires future exploration and development in the marine context (van Putten et al 2018b), especially for enhancing marine citizenship. Marine citizenship, i.e., an individual's rights and responsibilities regarding the marine environment, necessitates increased awareness about marine issues, adequate understanding about the personal role and behavior involved in creating and solving these issues, and a positive shift in values that can promote ocean-friendly, proenvironmental behavioral decisions (McKinley and Fletcher 2012).…”
Section: Think That Is Very Very Powerful When You Get the Localsmentioning
confidence: 99%